Terjemahan Ungkapan Slang dalam Novel To All The Boys I’ve Loved Before karya Jenny Han - Harahap, Annisah Inriani; Saragih, Erikson; Rosa, Rusdi Noor (Jurnal Bahasa dan Sastra, 2024)
The current issue in the translation process is the inappropriate choice of technique, which affects the accuracy and acceptability of the translation, as well as the need to identify slang expressions from the source language to the target language to ensure the style aligns with the target language's characteristics. Therefore, this study aims to analyze the techniques used to translate slang expressions from English (the source language) into Indonesian (the target language) using the theories of Butkuiviena and Petrulionē (2010), and Vinay and Darbelnet (1995) in the novel To All The Boys I've Loved Before, while also analyzing the linguistic style of the slang translation from English into Indonesian using Joos's theory (1967). The research method employed is qualitative, with document analysis for data collection. Meanwhile, the data analysis method uses thematic analysis. The results show that the most dominant technique used by translators for translating slang expressions is the literal technique. This finding suggests that the literal translation technique is generally capable of accommodating and sufficiently accurate in translating slang expressions in this novel, which features light and casual language use. Given that the novel narrates a simple teenage story, the dominant linguistic style in the translation of slang expressions is casual style. This finding reflects that the novel's style closely resembles the preferred linguistic style of young readers, who tend to be more relaxed, friendly, and open.